Biaxial flexural strength of Turkom-Cera core compared to two other all-ceramic systems. - Al-Makramani, B.M.A.lah; Razak, A.A.A.; Abu-Hassan, M.I. (2010)
Turkom-Cera core had significantly higher flexural strength than In-Ceram and Vitadur-N ceramic core materials.